Application of the ratio of the radiopaque calcified area to the dental follicle (RCA/DF) for dental age assessment on orthopantomograms. (November 2022) - Lian, Xiaoli; Dai, Xiaohua; Yan, Yan; Lei, Han; Wang, Guanhua; Li, Ruixin; Wang, Yue; Zou, Huiru
Abstract: Objectives: This study aimed at exploring a new tooth development evaluation method for age assessment and investigating the dynamic alteration and potential trend of tooth development by orthopantomograms (OPGs), in order to provide references for tooth development prediction and forensic purpose. Materials and methods: A total of 132 OPGs of children aged 3–8 years were collected. The developmental stages of the permanent mandibular second molar (M2)were evaluated by experienced examiners according to the Nolla method and Mimics software, respectively. Quantitative analysis of the ratio of the radiopaque calcified area to the dental follicle (RCA/DF) in different stages, ages, sexes and quadrants were evaluated and compared via descriptive statistics and Spearman's correlation coefficient analysis. Results: There was a strong, positive correlation between the examiners' evaluation and mimics analysis results. With the age increased, the Nolla stage of M2 observed by OPGs increased, and the RCA/DF showed increased trends both in males and females. There were significant differences of the RCA/DF of the M2 at various ages. The tooth calcification development of female was 9.08% earlier than that of male between 3 and 8 years old. However, teeth of male seemed to develop faster than that of female during this period. There was no significant difference between left and right quadrant either according to the Nolla stage or RCA/DF. Conclusions: The RCA/DF value obtained from OPGs of the developmental mandibular second permanent molars could be used as a reliable indicator for tooth maturity and age estimation in children aged 3–8 years. Clinical relevance: Age assessment based on radiographs is considered as a reliable and efficient indicator for judging different types of malocclusion, making suitable orthodontic treatment plan, deciding the extraction time of retained deciduous teeth in clinic practice. Highlights: A novel quantitative dental assessment with orthopantomograms was raised. The mathematical model of the tooth germ development with age was established. The ratio of radiopaque calcified area to the dental follicle could estimate age. The index of tooth germ development stage was appropriate for forensic purposes.